2021
DOI: 10.1080/12298093.2021.1936766
|View full text |Cite
|
Sign up to set email alerts
|

Tour of Truffles: Aromas, Aphrodisiacs, Adaptogens, and More

Abstract: Truffles are the fruiting bodies of ascomycete fungi that form underground. Truffles are globally valued, culturally celebrated as aphrodisiacs, and highly sought-after delicacies in the culinary world. For centuries, naturalists have speculated about their mode of formation, and in cultures surrounding the Mediterranean Sea, many species have been prized as a delectable food source. Truffle fruiting bodies form underground and emit a variety of volatile organic compounds (VOCs). Truffle volatiles are believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…Preclinical studies in mice demonstrated that alterations in GnRH neuronal function in addition to blunt learning abilities could also alter the ability of subjects to discriminate odours (Manfredi‐Lozano et al, 2022). Scent‐detecting dogs have been used to identify specific odours for a long time (Allen & Bennett, 2021; Moser et al, 2019; Simon et al, 2020). Despite the fact that the trainability of dogs may depend on sex, for example with respect to drug detection performance, males appear to perform better in drug detection training than females, neutered dogs of both sexes were shown to be less trainable than intact animals (Abdel Fattah & Abdel‐Hamid, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in mice demonstrated that alterations in GnRH neuronal function in addition to blunt learning abilities could also alter the ability of subjects to discriminate odours (Manfredi‐Lozano et al, 2022). Scent‐detecting dogs have been used to identify specific odours for a long time (Allen & Bennett, 2021; Moser et al, 2019; Simon et al, 2020). Despite the fact that the trainability of dogs may depend on sex, for example with respect to drug detection performance, males appear to perform better in drug detection training than females, neutered dogs of both sexes were shown to be less trainable than intact animals (Abdel Fattah & Abdel‐Hamid, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Risotto, pasta, pizza, omelet, salad, and polenta are just some popular dishes that are commonly served with a topping of white truffle slices. 3,6 Only two species predominantly share the white truffle market: Tuber magnatum Picco, yielding the Alba truffle or Piedmont truffle, and Tuber borchii Vittad., previously named Tuber albidum, yielding the Bianchetto truffle. 1,3,5,7 Both species are native to Europe.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,6 Only two species predominantly share the white truffle market: Tuber magnatum Picco, yielding the Alba truffle or Piedmont truffle, and Tuber borchii Vittad., previously named Tuber albidum, yielding the Bianchetto truffle. 1,3,5,7 Both species are native to Europe. The occurrence of T. magnatum is not limited to the Piedmont region of Italy, but this species is also found in other Italian regions, in Croatia, Hungary, Romania, and Slovenia.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuber spp., commonly known as truffles, belong to the family Tuberaceae in the order Pezizales, phylum Ascomycota. The truffle fruiting bodies are valuable because of their specific aroma and are expensive delicacies due to the decreasing yields of wild truffles and unpredictability of cultivation ( Allen and Bennett, 2021 ). Tuber spp.…”
Section: Introductionmentioning
confidence: 99%